The Participation of Employees in Building the Company's Image - Tienni Mariana Simanjorang; Roso Witjaksono; Nafly Comilo Tiven (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze the participation of employees in building the corporate image of PT Sang Hyang Seri Persero UBD Klaten Office. The research unit is all employees in the UBD Klaten Regional Office, which is as many as 30 people as a sample. The analysis was carried out by qualitative descriptive analysis with Likert analysis tools. The results showed that the total distribution of employee participation in building the company's image was in the low category. Employee participation in the form of quality assurance has a high participation compared to employee participation in service, social interaction and self-appearance